Transformation of Indonesian Police Human Resources Management in The Digital Era: Opportunities and Challenges - Elka Rudlof Saputro Nugroho; Pudji Astuty (PT. ALHAFI BERKAH INDONESIA, 2025)
This study aims to examine the transformation of human resource management (HR) in the Indonesian National Police (POLRI) in facing the digital era, by highlighting the opportunities and challenges that arise. The method used is a qualitative approach with data collection techniques through in-depth interviews with POLRI personnel and literature analysis (library research) on policies, regulations, and previous studies related to the digitalization of HR management. The research results indicate that digitalization opens up opportunities for recruitment efficiency, e-learning-based training, and real-time performance monitoring. However, significant challenges were also found, such as limited technological infrastructure, resistance to changes in organizational culture, and the need to improve personnel's digital competence. The transformation of POLRI HR management requires adaptive strategies and visionary leadership to align digital demands with the values of police professionalism. This study is expected to be a strategic reference in the development of technology-based POLRI HR policies.